Pengembangan Sistem Penyimpanan Data Sensor IoT Berbasis Permissioned Blockchain dengan menggunakan Platform Hyperledger - Arya Wardhana Budi Utomo; Adhitya Bhawiyuga; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The use of IoT technology in everyday life will produce a lot of data containing user data privacy. In this era the use of cloud to store IoT data involves the privacy of user data related to data management provided by cloud providers. Therefore, a data storage system that can protect the privacy of user data is needed so that the threat of privacy of user data can be minimized. One technology that can be used to store data and protect data privacy is blockchain. As one solution to solve the privacy issues of user data in data management centered on the cloud, this study create an IoT sensor data storage system that applies permissioned blockchain by using the Hyperledger platform. Hyperledger choosed to get short storage validation time. The results of the implementation of this research are systems that can store, change, and take IoT data sensors on the blockchain. Then, user privacy data is maintained with access controls and channels on the blockchain. Latency test shows the data storage time is increase in accordance with the number of IoT data sensors that will be saved.